Chronological framework of the Ailaoshan metamorphic belt, southeastern Tibet: implications for Cenozoic tectonothermal evolution - Xiao-Fei Guo; Qing-Long Wang (All Earth)
The response mechanism of the southeastern Tibet Plateau to the Indian-Eurasian collision is still controversial. The widely distributed shear systems in the Sanjiang area especially Ailaoshan-Red River shear system contribute a window to understand the tectonic evolution. Here we compile comprehensive geochronological data of the high-grade metamorphic rocks from the Ailaoshan-Red River shear system. The data reveal that the Ailaoshan metamorphic belt should be metamorphic complex with Middle-Late Triassic magmatic rocks and Cenozoic granites besides the Precambrian basement. The Cenozoic U-Pb age results of granitic rocks by accessory mineral within the Ailaoshan-Red River shear system range from ~41 Ma to ~20 Ma. The results of Ar-Ar dating of various minerals are in the range of ~40–5 Ma, concentrated in ~35–20 Ma. The U-Pb age results coincide basically with Ar-Ar data, indicating a rapid cooling process and reflecting a possible tectonic transition at ~20 Ma. The metamorphism and magmatism since the Cenozoic were not only unique to the Ailaoshan metamorphic belt, but also existed in the Chongshan and Gaoligongshan metamorphic belts. We infer that the Sanjiang area has a similar lateral extrusion deformation background and corresponds to the response of the India-Eurasia convergence process.